EFEKTIVITAS PENERAPAN UU. No. 13 TAHUN 2011 PADA PENANGANAN FAKIR MISKIN DALAM PERSPEKTIF EKONOMI ISLAM DI DINAS SOSIAL KABUPATEN BEKASI - Nurhasanah, Putri; Achmad, Yudianto; Ainulyaqin, Muhammad Hamdan; Edy, Sarwo (Jurnal Ilmiah Ekonomi Islam, 2023)
This research reveals a form of the effectiveness of the application of Law no. 13 of 2011 on handling the poor in an Islamic economic perspective at the Bekasi District Social Service seen from five indicators which include program understanding, right on target, on time, achieved goals, real changes. The findings of this study, among other things, revealed that the three indicators of effectiveness carried out by the Social Service of Bekasi Regency, namely understanding of the program, being on time, the real changes that have been explained in the discussion show that the application of Law No. 13 of 2011 in handling the poor in the Social Service of Bekasi Regency indicates the criteria "Effective". However, on the other two indicators of effectiveness, namely being right on target, achieving the objectives in the discussion, it shows that the application of Law No. 13 of 2011 to the handling of the poor at the Social Service Office of Bekasi Regency shows the criteria "Not Yet Effective". Furthermore, regarding the effectiveness of the implementation of Law no. 13 of 2011 on handling the poor in an Islamic economic perspective explains that showing the criteria of "Effective" is in accordance with an Islamic economic perspective.